inggris - Agustinus Tamo Bapa; Slamet; Hery Susanto (Journal of Mathematics Education and Science, 2025)
Problem-solving skills are essential in facing current challenges and developments. This study aims to describe students' ability to solve mathematical problems in the form of matrix story problems. This study employs a qualitative descriptive method and involves 93 eleventh-grade high school students. The instrument used is a written test consisting of two problem-solving questions. Subject selection was based on the results of a problem-solving ability test. Data collection utilized the problem-solving ability test questions and interviews. Qualitative data analysis was conducted through data reduction, data presentation, and conclusion drawing. The analysis was conducted according to Polya's model. The results showed that 7 students (8%) had very good mathematical problem-solving skills, as they were able to complete all four stages of Polya's model. Another 19 students (20%) were categorized as having good skills, although they only completed three stages of Polya's model without performing the final verification stage. Meanwhile, 30 students (32%) were only able to complete two stages of Polya's model without fully understanding the problem and without conducting a recheck, thus categorized as having adequate problem-solving skills. Additionally, 37 students (40%) were only able to complete one stage of Polya's model without fully understanding the problem, without formulating a plan, executing the plan, and without conducting a recheck. Thus, they were categorized as having poor problem-solving skills. This indicates that each student's ability to understand the problem, develop a problem-solving plan, implement the problem-solving plan, and check the answers is still in the low category. Therefore, it can be concluded that students' mathematical problem-solving abilities are still low. It is hoped that teachers can train students in learning, conduct effective learning, and thus improve students' problem-solving abilities.